Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dengan Employee Engagement sebagai Variabel Pemediasi Studi di BPRS Yogyakarta - Nevi Laila Khasanah (El-Ghiroh : Jurnal Studi Keislaman, 2019)
Employee performance is employee productivity and output as a result of employee development which will ultimately affect the effectiveness of the organization (Hameed and Waheed, 2010). The main objective of this study was to analyze the effect of employee engagement in mediation influence of transformational leadership on employee performance. The data used in this study are primary data obtained through survey method by distributing questionnaires. Multifactor Leadership Questionnaire (MLQ) was used to assess employee perceptions of transformational leadership characteristics. Utrecht Work Engagement Scale (Uwes) was used to assess levels of employee engagement. The Role-Based Performance Scale was used to assess the performance of employees. The questionnaire used is measured using a Likert scale. Testing a variable on other variables is done by simple linear regression test and mediation models tested by the method of hierarchical regression analysis by Baron and Kenny (1986). The results of this study indicate that the role of transformational leadership and significant positive effect on employee engagement and employee performance. The results of this study also showed that employee engagement on employee partially mediate the relationship transformational leadership.